Utilization Pattern of Analgesics in Orthopedic in-Patient Department at Tertiary Level Teaching Hospital in Dhaka - Akter Khatun, Shima; Ahmed, Sumaiya; Hossain Mondal, Mosaddek; Bin Hossain, Rashel; Chanda Shaha, Kartick; Saha, Shusmita (Medicine Today, 2025)
Introduction with Objective: The aim of this study was to evaluate the utilization pattern of analgesics in orthopedic in-patient department at tertiary level teaching hospital in Dhaka. Materials and Methods: An observational, cross-sectional study was carried out for 6 month from July 2018 to December 2018. Collected data were age, sex, number of the drugs, co-prescribed drugs along with analgesic during the study period. The patients details were recorded in a predegined data collection form and results were analyzed by SPSS Version (20.1). Results: Out of 200 patients, 123 were male and 77 were female. Out of 200 patients, most of the patients belonged to 41-50 years (30%). In this study, 55.5% of patients had received single analgesic. Ketorolac was the most commonly prescribed analgesic (43.49%). During hospitalization, majority of the patients have received parenteral preparation. Gastroprotective agents were frequently prescribed along with analgesics. Conclusion: The percentages of analgesics were found satisfactory. Regular educational interventions to improve prescribing practices among physicians at different levels may further promote rational prescribing. Medicine Today 2025, Vol.37 (1): 111-113